2021
DOI: 10.1039/d1sc02120f
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative stabilisation of 14-3-3σ protein–protein interactions via covalent protein modification

Abstract: 14-3-3 proteins are an important family of hub proteins that play important roles in many cellular processes via a large network of interactions with partner proteins. Many of these protein-protein...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Synthetic peptides that mimic the binding motifs of the phosphorylated partner protein to 14-3-3 have a sufficiently small size relative to 14-3-3 and can be modified to incorporate a fluorescent label. Their use in place of the natural protein partner makes FP a particularly versatile technique for studying In this review of recent 14-3-3 literature, we have identified 15 studies that used FP as part of the analytical workflow (Soini et al, 2021a;Cossar et al, 2021;Falcicchio et al, 2021;Gogl et al, 2021;Guillory et al, 2021;Horvath et al, 2021;Ruks et al, 2021;Sijbesma et al, 2021;Centorrino et al, 2022;Hazegh Nikroo et al, 2022;Joshi et al, 2022;Srdanovic et al, 2022;Srdanović et al, 2022;Stevers et al, 2022). Because it is such a well-established technique, here we focus on select examples that demonstrate how FP can be used to address three key challenges in current 14-3-3 research: (i) Quantifying the cooperative nature of 14-3-3 molecular glues; (ii) Understanding 14-3-3 isoform specificity and partner protein binding mechanisms; (iii) Studying the kinetic characteristics of 14-3-3 PPIs.…”
Section: Fluorescence Polarisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Synthetic peptides that mimic the binding motifs of the phosphorylated partner protein to 14-3-3 have a sufficiently small size relative to 14-3-3 and can be modified to incorporate a fluorescent label. Their use in place of the natural protein partner makes FP a particularly versatile technique for studying In this review of recent 14-3-3 literature, we have identified 15 studies that used FP as part of the analytical workflow (Soini et al, 2021a;Cossar et al, 2021;Falcicchio et al, 2021;Gogl et al, 2021;Guillory et al, 2021;Horvath et al, 2021;Ruks et al, 2021;Sijbesma et al, 2021;Centorrino et al, 2022;Hazegh Nikroo et al, 2022;Joshi et al, 2022;Srdanovic et al, 2022;Srdanović et al, 2022;Stevers et al, 2022). Because it is such a well-established technique, here we focus on select examples that demonstrate how FP can be used to address three key challenges in current 14-3-3 research: (i) Quantifying the cooperative nature of 14-3-3 molecular glues; (ii) Understanding 14-3-3 isoform specificity and partner protein binding mechanisms; (iii) Studying the kinetic characteristics of 14-3-3 PPIs.…”
Section: Fluorescence Polarisationmentioning
confidence: 99%
“…FP has been widely used to screen and profile molecular glues from established examples such as fusicoccin A through to novel fragments, macrocycles and peptide-conjugates. Typically, the effect of a glue is quantified either: 1) by performing 14-3-3 protein titrations in the presence of a fixed concentration of the glue or inhibitor and partner peptide, and comparing the effective K d observed to that of a control experiment (see in Figure 2A ); or 2) by performing ligand titrations to fixed concentrations of 14-3-3 protein and partner peptide to calculate “EC 50 ” values (see in Figure 2B ) ( Soini et al, 2021a ; Falcicchio et al, 2021 ; Guillory et al, 2021 ; Sijbesma et al, 2021 ; Wolter et al, 2021 ; Centorrino et al, 2022 ; Srdanovic et al, 2022 ; Stevers et al, 2022 ). However, both of these approaches are concentration dependent and the values obtained differ depending on experimental design (i.e., the concentration of the fluorophore in protein titrations, or the concentration of the 14-3-3 protein in ligand titrations).…”
Section: Fluorescence Polarisationmentioning
confidence: 99%
See 3 more Smart Citations